Effectiveness of a Program to Improve the Verbal Response of Football Coaches: A Delayed-Intervention Experimental Design - Federico Leguizamo; Antonio Núñez Prats; Elena Gervilla; Jordi Llabrés; Alex Garcia-Mas (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The pressure that coaches usually apply on their athletes, alongside injuries and the lack of enjoyment during sport practice, are key factors involved in sports abandonment. Behavioral interventions through psychoeducational programs have proven to be useful to improve coaching behaviors, providing appropriate context in sports. This study aims to assess a brief psychological intervention in football coaches to reduce potentially harmful verbal responses and increase the use of positive feedback. Our research was conducted in an amateur football club where 15 coaching staff teams agreed to participate. The experimental design of this study is a randomized controlled trial with control (n=7) and experimental (n=8) groups with delayed intervention. Verbal responses from coaches were collected as count data with an adapted version of the Coaching Behavior Assessment System. Data was analyzed using the Poisson Regression Model. The results show a reduction in hostile feedback by 87.7% (CI = 71% - 94.9%), technical instructions with ball in play by 39.8% (CI = 24.2% - 52.2%), complaints to referees by 95.8% (CI = 82.8% - 99.3%) and an increase in praise contingent with successful action y 87% (CI = 13% - 209%) after the intervention. These findings have important implications for the implementation of programs that seek to improve delivery of instructions in sport coaches, providing a thorough procedure for the shaping of the verbal response. Valuable insights to foster a supportive learning environment for adolescents and young athletes are addressed in the discussion.